2020
DOI: 10.1177/1060028020962037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acute Postoperative Pain Management During an Injectable Opioid Shortage

Abstract: Background: Drug product shortages, including injectable opioids, are common and have the potential to adversely affect patient care. Objective: To evaluate the impact of an injectable opioid shortage for hospitalized adult patients in the acute postoperative setting. Methods: A single-center, retrospective cohort study of noncritically ill hospitalized, postoperative patients requiring opioids for acute pain management was conducted. Patient cohorts were compared preshortage and postshortage for proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is, in effect, "deprescribing without a license" by denying access to medications which may be safer when considering differences in pharmacology with Phase I metabolism (hydrocodone and oxycodone) versus Phase II metabolism (hydromorphone and morphine) and potential for comorbidities. 11 Other subsequent commentaries and studies have confirmed the challenges associated with treating inpatients' pain due to the APQ reductions, [12][13][14][15][16][17][18] including those addressing treating children perioperatively and postoperatively. 19,20 Up to this point, reports of APQ reduction-related shortages of oral opioids are only anecdotal, with numerous reports from patients on social media.…”
mentioning
confidence: 99%
“…This is, in effect, "deprescribing without a license" by denying access to medications which may be safer when considering differences in pharmacology with Phase I metabolism (hydrocodone and oxycodone) versus Phase II metabolism (hydromorphone and morphine) and potential for comorbidities. 11 Other subsequent commentaries and studies have confirmed the challenges associated with treating inpatients' pain due to the APQ reductions, [12][13][14][15][16][17][18] including those addressing treating children perioperatively and postoperatively. 19,20 Up to this point, reports of APQ reduction-related shortages of oral opioids are only anecdotal, with numerous reports from patients on social media.…”
mentioning
confidence: 99%